My life matters: The cost of being a Black youth - Edwards, Fiona (My University, 2021)
White supremacy presents Black communities with numerous challenges. We are constantly being injured by the anti-black racism that is deeply entrenched in the policies and practices of dominant institutions. These establishments, including, if not especially, the criminal justice system, purport to be responsible for ensuring the well-being and welfare of all, but only ever protect the rich and white. The recent re-mobilization ofbthe Black Lives Matter movement worldwide has reminded the public of the urgency of tackling anti-black racism, but much work still needs to be done if we want future generations of Black people to live freely. Like Black adults, Black youth are not immune from racist encounters. In such a time of racial crisis, the experiences of Black youth need to be centralized in a movement that opposes racial injustice and white supremacy. Accordingly, this poem adopts the lens of a Black youth to speak to the cost of growing up Black immersed in the dominant anti-black culture of our society, underscoring the troubling realities of what it means to be a Black youth in today’s world.
Keywords: Black youth; racial injustice; whiteness; systemic oppression